(untitled) (Altre Modernità, 2025)
The crisis of political representation to which the ‘Indignados’ movement, or 15M, gave voice has redefined Spanish political life with consequences traceable to the present day. In the cultural sphere, a crisis of representation has also been discussed, although the term has been used in a looser sense to refer to a paradigm shift rather than a crisis of representation proper. This study aims to take a first step towards addressing that gap by explaining, through a harmonisation of Badiou’s theory of the ‘event’ with cultural semiotics, the link between the two crises -political and artistic- which we propose to understand as a crisis of certain processes of symbolic mediation that entail reconfiguring the connections between language and reality. This crisis of symbolic mediation, in turn, has discernible effects on the arts, particularly evident in artistic and literary expressions. Through an analysis of the relationships between the conditions of art and politics, this text argues that, even if we cannot speak of an artistic event stricto sensu, the dawn of the 15M political event saw the consolidation of a series of literary manifestations that must be understood as (a) subject of that event, which we term 15M fiction.